Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1262/jrd.19017
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of Ewes Inseminated Intrauterinally with Frozen Semen Using Extender Containing Bovine Serum Albumin

Abstract: Abstract. The present study was conducted to examine the fertility of ewes inseminated intrauterinally with frozen semen using semen extender containing either egg yolk or bovine serum albumin (BSA). Sixty Suffolk and cross-bred ewes were treated with controlled internal drug release (CIDR) devices during the non-breeding season (July 2006). A CIDR was inserted into the vagina for 12 days and an intramuscular injection of 500 IU equine chorionic gonadotropin was administered one day before its removal. Ejacula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 18 publications
2
30
1
1
Order By: Relevance
“…The semen extenders were; AndroMed [6,7] and two Tris-based extenders containing 297.58 mM Tris, 96.32 mM citric acid, 82.66 mM fructose, 5% (v/ v) glycerol and either 15% (v/v) egg yolk [6,9] or 10% (w/v) BSA [6,8,10]. The three semen extenders have been defined here as AM, BSA and EY for the AndroMed, Tris-based BSA-containing and Tris-based egg yolk-containing solutions, respectively.…”
Section: Semen Preservationmentioning
confidence: 99%
See 1 more Smart Citation
“…The semen extenders were; AndroMed [6,7] and two Tris-based extenders containing 297.58 mM Tris, 96.32 mM citric acid, 82.66 mM fructose, 5% (v/ v) glycerol and either 15% (v/v) egg yolk [6,9] or 10% (w/v) BSA [6,8,10]. The three semen extenders have been defined here as AM, BSA and EY for the AndroMed, Tris-based BSA-containing and Tris-based egg yolk-containing solutions, respectively.…”
Section: Semen Preservationmentioning
confidence: 99%
“…Our recent studies [6][7][8] on artificial insemination (AI) in sheep have clearly shown that a soybean-based semen extender (AndroMed) is useful and comparable to the conventional semen extenders containing egg yolk or BSA. Fukui et al [6] compared the fertility of ewes inseminated intrauterinally with frozen semen using AndroMed (AM) and Tris-based extenders containing BSA or egg yolk and found similar lambing rates among the three semen extenders (56.7, 55.2 and 64.5% for AM and semen extenders containing BSA or egg yolk, respectively).…”
mentioning
confidence: 99%
“…A soybean lecithin-based extender (AndroMed; Minitub, Tiefenbach, Germany) has been developed and utilized for bovine [7][8][9] and mountain gazelle semen [10]. Fresh and frozen ram semen diluted with a synthetic semen extender, AndroMed, has been inseminated with satisfactory fertility results in Norway (Paulenz H.: personal communication).Low fertility (20-30%) in ewes inseminated with frozen semen into the cervical orifice, an ordinal deposition site for artificial insemination (AI) in sheep, has not been applied fully on the field, except for intrauterine AI using laparoscopy (60-80% in lambing rates) [11][12][13][14][15]. In Norway, Paulenz et al [16,17] inseminated frozen ram semen into either the cervical orifice or deep vagina and obtained a lambing rate of 70%.…”
mentioning
confidence: 99%
“…Half the volume of each insemination dose (0.2 ml) was deposited into each uterine horn using an insemination pipette (No. 20887; I.M.V., Rue ClĂ©menceau, France) with the aid of laparoscopy [11][12][13][14][15].Pregnancy was diagnosed 60 days after AI by real-time ultrasonic scan. Lambing rate (number of ewes lambed/number of ewes inseminated) and prolificacy (number of lambs born/number of ewes lambed) were recorded.…”
mentioning
confidence: 99%
“…Ewe breed is also a significant source of variation in fertility after AI (Donovan, et al, 2004;Fukui, et al, 2007;Papadopoulos, et al, 2005;Salamon & Maxwell, 1995). Differences in the mean time of ovulation and ovulation rates in different breeds of ewes at differences locations may explain the variation in fertility (Salamon & Maxwell, 1995).…”
Section: Breedmentioning
confidence: 99%